Effect of storage on breast milk antioxidant activity. Issue 6 (21st October 2004) - Hanna, N; Ahmed, K; Anwar, M; Petrova, A; Hiatt, M; Hegyi, T
Abstract : Background: Human milk, which contains compounds beneficial to infants, is often expressed and stored before use. Changes in its antioxidant activity with storage have not been studied. Objectives: To measure antioxidant activity of fresh, refrigerated (4°C), and frozen human milk (−20°C), stored for two to seven days; to compare the antioxidant activity of milk from mothers delivering prematurely and at term; to compare the antioxidant activity of infant formulas and human milk. Methods: Sixteen breast milk samples (term and preterm) were collected from mothers within 24 hours of delivery and divided into aliquots. Fresh samples were immediately tested for antioxidant activity, and the rest of the aliquots were stored at −20°C or 4°C to be analysed at 48 hours and seven days respectively. The assay used measures the ability of milk samples to inhibit the oxidation of 2, 2′-azino-di-3-(ethylbenzthiazolinesulphonate) to its radical cation compared with Trolox. Results: Antioxidant activity at both refrigeration and freezing temperatures was significantly decreased. Freezing resulted in a greater decrease than refrigeration, and storage for seven days resulted in lower antioxidant activity than storage for 48 hours. There was no difference in milk from mothers who delivered prematurely or at term. Significantly lower antioxidant activity was noted in formula milk than in fresh human milk. Conclusions: To preserve the antioxidant activity of human milk, storage time should be limited to 48 hours. Refrigeration is better than freezing and thawing.